DESIGN AND IMPLEMENTATION OF TIME OF FLIGHT (TOF) DATA PROCESSING IN AN ACOUSTIC TOMOGRAPHY DEVICE (TERAWANG) FOR MONITORING THE INTERNAL CONDITION OF TREES - Aji Nugroho, Bayu
In the process of maintaining and managing trees in Ruang Terbuka Hijau (RTH) environments, several institutions, such as government agencies and educational institutions, require third-party assistance to observe and assess the health condition of planted trees. This activity necessitates tree maintenance and management consultants, such as tree researchers, arborists, and forestry lecturers, who can effectively analyze tree conditions. However, to date, tree researchers primarily rely on visual assessment methods and Forest Health Monitoring (FHM) to evaluate tree health. These methods have limitations, as researchers cannot directly observe the internal condition of tree trunks. In fact, trunk structure is a crucial component that determines a tree's strength and stability, preventing it from collapsing. Therefore, the author and team have developed a device called Terawang, which can analyze the internal condition of tree trunks based on two-dimensional tomography images generated by the device. The tomography images produced by the Terawang device are derived from processing the propagation speed of acoustic waves within the tree trunk, as detected by sensors. The acoustic wave propagation speed is obtained by dividing the distance between sensors by the propagation time of the acoustic wave between two sensors. The calculation of acoustic wave propagation speed is performed by the Terawang application, installed on a smartphone, while considering the tree's geometric data. The tree geometry data is manually measured using a tree diameter tape and then input into the Terawang application. Meanwhile, the calculation of acoustic wave propagation time (Time of Flight/ToF) is obtained from a microcontroller timer based on the detection of digital signals from eight sensors arranged around the tree at a predefined distance. The ToF value is determined by the time difference between the peak of the acoustic signal received by the receiving sensor and the source sensor. This time difference is measured using a microcontroller timer with a precision of 1 microsecond. The ToF data collected from all eight sensors is transmitted wirelessly to the application, where it is processed into propagation speed data and subsequently displayed in the Terawang application. The propagation speed data from each sensor is then used by the iv application to generate a two-dimensional tomography image, representing the tree's internal condition. Within the overall Terawang system, the author focused on the design and implementation of Time of Flight (ToF) data processing. This component consists of three subsystems: the data acquisition subsystem, which utilizes a KY-037 sensor as its main component; the control and data processing subsystem, which employs a Teensy 4.1 microcontroller; and the wireless communication subsystem, which incorporates a HC-05 Bluetooth module. Based on implementation and testing, the ToF data processing functions effectively, enabling the Terawang application to process and display propagation speed data. Testing conducted on a 50 cm diameter cross-section of Trembesi wood revealed that the standard deviation was less than 10 microseconds for reference sensors 1, 2, 3, 4, 6, 7, and 8. Meanwhile, for reference sensor 5, the standard deviation ranged between 15–20 microseconds. The accuracy and precision of the test results are influenced by the sensitivity level of each sensor.